Characterization And Properties Of Carboxymethyl Celluloses – Oil Palm Empty Fruit Bunch Hemicelluloses Blend And Nanocomposite Films - Razak, Nadhilah Muhammad (2018)
In this study, hemicelluloses were successfully extracted from oil palm empty fruit bunch. Hemicelluloses produced through alkali-ethanol extraction technique. The hemicelluloses then blended with carboxymethyl cellulose (CMC) at various hemicelluloses loading (20, 40, 60, and 80 wt %) by using solution casting method to produce hemicelluloses-carboxymethyl cellulose (H-CMC) blend films. Montmorillonite (MMT) with 2 % was added to enhance the properties of the (H-CMC-MMT) nanocomposite films. The effect of blending ratio and the effect of MMT loading on the physico-chemical, mechanical, thermal and barrier properties of nanocomposite films were successfully analyzed and characterized. The films were characterized by mean of scanning electron microscopy (SEM), fourier transform infrared spectroscopy analysis (FTIR), X-ray diffraction (X-RD), differential scanning calorimetry (DSC), thermogravimetry (TGA), tensile strength, molecular weight, water vapor permeability, contact angle and biodegradability analysis. FTIR analysis revealed the peak of carbonyl group that representing hemicellulose intensity increases with additional of hemicelluloses for all H-CMC blend films. Thermal analysis shows the melting temperature was shifted to higher temperature from 258.34 ºC to 260.14 ºC by 1.8 % of high loading hemicelluloses at 80 % compared to pure CMC films. SEM observation revealed uniform and smooth surface of H-CMC blend films up to 40 % hemicelluloses loading before the roughness occurred at 80 % hemicelluloses loading. The elongation at break of hemicelluloses blend films increased by 14.30 %, however the tensile strength of the hemicelluloses blend films decreased by 56 % when 80 % hemicelluloses loading was used compared to CMC films. Compared to the blend films, the nanocomposite films shows excellent tensile strength of films by (29.6 MPa), which was 15.2 % higher than the blend film. The nanocomposite films enhanced the tensile strength due to the effect of the strong hydrogen bonding and electrostatic interaction between CMC and MMT. In addition, the nanocomposite films had high thermal behavior and low water vapor permeability. These observations suggest that the blend film can be uses in area of application in the coating and packaging industry.